Flooding tolerance of Paspalum dilatatum (Poaceae: Paniceae) from upland and lowland positions in a natural grassland - Mollard, Federico Pedro Otto (2008)
The grass Paspalum dilatatum Poir. subsp. dilatatum inhabits periodically flooded lowlands as well as non-flooded uplands of the flooding Pampa grasslands (Argentina), while P. dilatatum Poir. subsp. flavescens Roseng., B.R. Arrill. & Izag. inhabits only the upland sites. An experiment was designed to determine if there is local adaptation to flooding in physiological, anatomical and leaf morphological traits. To this end, plants of these populations were subjected to flooding (6 cm water depth) and control conditions (watered daily) for 60 days in an experimental garden. Flooded plants of the subsp. dilatatum from the lowland had 35% higher photosynthesis compared to controls without affecting their stomatal conductance, transpiration rate and leaf water potential. By contrast, both subsp. dilatatum and subsp. flavescens from the upland did not increase their photosynthesis, and had reduced their stomatal conductance and leaf transpiration rate by 35% and 45% when growing in flooded conditions. Upland populations had higher leaf water potential with respect to controls. All populations had high constitutive root aerenchyma (28-42%), and leaf sheath porosity increased by 75% in flooded conditions (from 22-28% to 35-48%). Leaf lengthening differed among populations according to their habitat: subsp. dilatatum from the lowland was the only one that had longer leaf sheaths and blade lengths when flooded. In contrast, flooded plants of subsp. dilatatum from the upland only increased leaf sheath length while subsp. flavescens neither increased leaf blade nor leaf sheath. In conclusion, both the physiological performance and the leaf length plasticity differed among populations. The results agree with those expected based on the species' habitat, and indicate the better adaptation to the flood-prone habitat of P. dilatatum subsp. dilatatum taken from a lowland area.